“The mystery of this journey”: David Herbert Lawrence’s creative quest to discover true civilization - Mukherjee, Abhik (Creativity Studies, 2023)
David Herbert Lawrence is famous for telling us to trust the tale, not the artist. When we read the notoriously varied and vital Lawrence, there are many places where he seems to over reach, if not to outright contradict himself. This essay focuses on much of the complexity and ambiguity of Lawrence’s thought and its constantly evolving and even self-contradictory nature. Lawrence understands civilization with his utmost creativity and originality – finding the sun and relating it to the sexual vitality of the man – develops over the various travels. And in this essay, I focus on how this creative development is reflected in the travel writings. The more he travels, the more he discovers the subjugation of the self and the subsequent mechanization of it. The creative struggle to overcome this impotence informs Lawrence’s travel literature. His four travel books, namely Twilight in Italy (originally published in 1916), Sea and Sardinia (originally published in 1921), Mornings in Mexico (originally published 1927), and Sketches of Etruscan Places and Other Italian Essays (originally published 1932) are reflective of different stages in Lawrence’s journey to understand how human beings relate to the world they are integrally part of. Lawrence uses his travel to transcend his own nationality too. Lawrence goes on to assert that he belongs to no country. Surely this relates ironically to his belief in the “spirit of place”. The essay deeply focuses on his continued movement from place to place with deep consideration of this complex belief.